The Effects of Blades Number, Blade Thickness, Blade Tip Angle, and Twist Angle on the Performance of the Rotor Wind Turbines (Journal of University of Babylon for Engineering Sciences, 2021)
The paper gives an experimental study on the performance on the wind turbine rotors with several numbers of blades as well as twist angle. The main goal of this study is to demonstrate the effect blades number, tip angles as well as the twist angle of the blades on the power coefficient (Cp) of the rotor. Moreover, this result represents a simple evaluation about the range of depending power coefficient on the average wind speed.Also, this paper studies the performance of wind turbines which are tested by carrying out 2-dimensional dynamic using ANSYS-Fluent.